2019
DOI: 10.1007/s42452-019-1921-2
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical performances of activated carbon prepared using eggshell waste

Abstract: This paper describes the preparation of activated carbon (Ac) from broiler hen eggshell (BES) and Country hen eggshell (CES) waste with the assistance of chemical activating agent orthophosphoric acid (H 3 PO 4 ) and eggshell powder for 4:1 and 4:2 concentrations. XRD analysis affirmed the formation of Ac and the hexagonal structure of CaCO 3 for both BES and CES samples. The average crystalline size, dislocation density, microstrain, lattice parameter, and cell volume values are found to be higher for CES. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Wu et al [12] reported the successful fabrication of HA from oyster shell powder by solid-state reaction and subsequently heat treatment at 900-1100 • C. Recently, our research group [13] proposed an environmentally beneficial and cost-effective method of preparing HA or tri-calcium phosphate (TCP) bioceramics from eggshell biowaste. The eggshell mainly consisted of a major component, i.e., calcium carbonate (94%), besides calcium phosphate (1%), magnesium carbonate (1%), and organic matter (4%) [14]. It is worth mentioning that the crystal structure and composition of HA prepared from natural sources like eggshells are similar to those of human bones because eggshells notably contain several trace elements (Na, Mg, Sr, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…Wu et al [12] reported the successful fabrication of HA from oyster shell powder by solid-state reaction and subsequently heat treatment at 900-1100 • C. Recently, our research group [13] proposed an environmentally beneficial and cost-effective method of preparing HA or tri-calcium phosphate (TCP) bioceramics from eggshell biowaste. The eggshell mainly consisted of a major component, i.e., calcium carbonate (94%), besides calcium phosphate (1%), magnesium carbonate (1%), and organic matter (4%) [14]. It is worth mentioning that the crystal structure and composition of HA prepared from natural sources like eggshells are similar to those of human bones because eggshells notably contain several trace elements (Na, Mg, Sr, etc.).…”
Section: Introductionmentioning
confidence: 99%
“…The pyrolysis reaction was finished as a result [14] The peak at 2 value was 28.3, which is evidence that this could be the carbon structure of graphite [15]. Its crystalline nature is represented by the peak 2 range at 40.41 [16]. MFPAC that has been plasmatreated gains intensity without altering its nature or structure.…”
Section: Xrd Analysismentioning
confidence: 92%
“…ICP analysis was carried out using inductively coupled plasma optical emission spectrometry (ICP-OES) (Prodigy XP, Teledyne Leeman). The proximate and physical parameters such as ash content, moisture content, tap density, and bulk density were determined using the standard methods as described by Balasubramanian et al The pH and electrical conductivity of ES and ES-SMF were determined in 1:10 (1 g of material: 10 mL of water) suspension.…”
Section: Methodsmentioning
confidence: 99%